Development of a Watershed‐Based Geospatial Groundwater Specific Vulnerability Assessment Tool. Issue 1 (22nd May 2014) - Baloch, Mansoor A.; Sahar, Liora
Abstract This study assesses and characterizes the vulnerability of unregulated groundwater systems to microbial contamination in 18 counties in the state of Georgia using a contamination risk screening strategy based on watershed characteristics and elements of the Safe Drinking Water Act's Wellhead Protection program. Environmental data sources analyzed include septic systems, elevation, land use and land cover data, soil, vegetation coverage, demographics, and livestock. A geospatial overlay/index modeling approach was developed to identify areas of higher vulnerability for groundwater pollution by taking into consideration watershed land use, hydrology, and topography (LHT). Sensitivity analysis was used to evaluate the effectiveness of model variables. The results of the model were validated by using field data and output from U.S. EPA's DRASTIC model, a widely used intrinsic vulnerability assessment tool. The validation showed a higher risk of microbial contamination for wells located in a high to medium LHT vulnerability zones. LHT provided a clear distribution of satisfactory and unsatisfactory wells in the three vulnerability zones; however, the majority of wells (>75%), with both satisfactory and unsatisfactory test results, are located in medium DRASTIC vulnerability zone. This difference between LHT and DRASTIC can be attributed to the microbial contamination specific factors incorporated into LHT index. It is concluded that although inclusion of potential contamination sources on adjacent land uses in the vulnerability assessment framework adds to the complexity of the processes involved in a vulnerability assessment, such inclusion provides a meaningful perspective to groundwater protection efforts as an effective screening tool.